Review: Hebrews. A New Translation with Introduction and Commentary - Browne, Arnold S. (The journal of theological studies, 2002)
Hebrews. A New Translation with Introduction and Commentary Craig R. Koester xii + 604 New York (The Anchor Bible.) Doubleday 2001 Hardback$47.50 0 385 46893 8